NLRP3, NLRP6, and NLRP12 are inflammasomes with distinct expression patterns - Wei, Bo; Billman, Zachary P.; Nozaki, Kengo; Goodridge, Helen S.; Miao, Edward A. (Frontiers in Immunology, 2024)
Inflammasomes are sensors that detect cytosolic microbial molecules or cellular damage, and in response they initiate a form of lytic regulated cell death called pyroptosis. Inflammasomes signal via homotypic protein-protein interactions where CARD or PYD domains are crucial for recruiting downstream partners. Here, we screened these domains from NLR family proteins, and found that the PYD domain of NLRP6 and NLRP12 could activate caspase-1 to induce cleavage of IL-1β and 2 GSDMD. Inflammasome reconstitution verified that full length NLRP6 and NLRP12 formed inflammasomes in vitro, and NLRP6 was more prone to auto-activation. NLRP6 was highly expressed in intestinal epithelial cells (IEC), but not in immune cells. Molecular phylogeny analysis found that NLRP12 was closely related to NLRP3, but the activation mechanisms are different. NLRP3 was highly expressed in monocytes and macrophages, and was modestly but appreciably expressed in neutrophils. In contrast, NLRP12 was specifically expressed in neutrophils and eosinophils, but was not detectable in macrophages. NLRP12 mutations cause a periodic fever syndrome called NLRP12 autoinflammatory disease. We found that several of these patient mutations caused spontaneous activation of caspase-1 in vitro, which likely causes their autoinflammatory disease. Different cell types have unique cellular physiology and structures which could be perturbed by a pathogen, necessitating expression of distinct inflammasome sensors to monitor for signs of infection.